PENGARUH PENAMBAHAN TEPUNG KEONG MAS (Pomacea canaliculata) PADA PAKAN UNTUK PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN LELE SANGKURIANG (Clarias gariepinus) - Nadila Chaerunissa, - (2022)
Lele sangkuriang is one of the most freshwater commodities that has a high demand to be cultivated and it requires intensive and optimal cultivation efforts to produce superior cultivars. The one effort is substituted commercial feed with golden snail flour which can be used as a protein for fish. This study aims to determine the effect of adding golden snail flour as a alternative feed for the growth and survival rate of lele sangkuriang (Clarias gariepinus). This research is conducted at Hatchery Universitas Pendidikan Indonesia Campus in Serang. The research method is used a completely randomized design experimental (RAL) method with 4 treatment levels and 3 repetitions. The results of ANOVA analysis show the addition of golden snail flour as feed has a significant effect for the growth of lele sangkuriang and has not significantly affect for the survival rate of lele sangkuriang (Clarias gariepinus). The result of datas within 30 days shows the highest length and weight has found in the PC treatment which has a significant effect with average length increase is 1.86 cm and average weight is 2.72 grams. The lowest feed conversion ratio value has found in the PC treatment is 1.33 and feed consumption is approximately 72,6 grams. The highest survival rate has found in PC treatment approximately 93.33%. The result of water quality parameters such as temperature is approximately 24,9˚C-25,5˚C, pH is approximately 6,0-6,55 and DO is approximately 2,2-5,2 ppm.